PEMBERDAYAAN MASYARAKAT TENTANG SWAMEDIKASI MELALUI EDUKASI GEMA CERMAT DENGAN METODE CBIA - Musdalipah Musdalipah (Universitas Lancang Kuning, 2018)
Smart Community Movement Using Drugs (GEMA CERMAT) is a community movement in raising awareness and understanding of the people about the use of drugs properly and correctly. Self medication is a treatment performed by the community without using a prescription. Through GEMA CERMAT it is expected that rational use of drugs by society can be achieved, including; knowledge of composition, indication, dosage and how to use, side effects, contra indications, and drug expiration dates. The Method of mother active Learning (CBIA) is an educational model of community empowerment to be more skilled in choosing medicine so that becomes more effective, safe, and cost-effective. This activity is aimed to know the improvement of public knowledge by giving education counseling of GEMA CERMAT in choosing over-the-counter and free drug limited by CBIA method. The event was conducted at the BTN Wirabuana complex of Kendari city in May 2017 with a pretest-posttest one-group pre-experimental design. Activities using questionnaires are processed by Chi-square test. Chi-square analysis results p = 0,000 <0.05 indicate an increase in public knowledge in choosing a drug free and limited free by CBIA method